Survey on Automated Text Documents Summarization Tools - S, Mr. Sagar; Bojewar, Prof.Sachin (IJRDO-Journal of Applied Science, 2015)
Text mining has become an important research field as it tries to discover valuable information from unstructured and large amount of texts. It becomes very difficult to get the relevant Information from the Unstructured and large amount of Single and Multiple Text Documents. Text Mining is an important task of Text Summarization. Automated Text Summarization is the Process of reducing the Original size of document without changing the overall meaning of the Text and achieving the relevant Information from the text documents. The goal of the Automated Text Summarization is to minimize the User’s time for reading and understanding the document without disturbing the User’s area of Interest. The Information Overload Problem can be easily overcome.